1991
DOI: 10.3168/jds.s0022-0302(91)78315-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Staphylococcus aureus from Sites Other than the Lactating Mammary Gland

Abstract: The body sites of 163 heifers, bedding and feedstuff samples, flies, and hands and nares of the research personnel were sampled in order to determine the sources of Staphylococcus aureus in a dairy herd other than the lactating mammary gland. Lesions on the udder of lactating animals and the air in the milking parlor were also sampled. Staphylococci isolated from bedding samples were identified as to species. Staphylococcus aureus was isolated from all sources examined except flies. An enrichment procedure was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
51
2
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 13 publications
7
51
2
3
Order By: Relevance
“…In addition, contact with a contaminated environment has been suggested (174). Such environment could also include the air, as studies have shown that air in pig and cow stables may contain considerable amounts of (antimicrobial resistant) bacteria (191,192).…”
Section: La-mrsa In Humansmentioning
confidence: 99%
“…In addition, contact with a contaminated environment has been suggested (174). Such environment could also include the air, as studies have shown that air in pig and cow stables may contain considerable amounts of (antimicrobial resistant) bacteria (191,192).…”
Section: La-mrsa In Humansmentioning
confidence: 99%
“…xylosus, the months June to November and June to August, respectively, were associated with higher odds for IMI, similar to the results of De Visscher et al (2017) who found an increased risk for presence of more relevant species in bulk tank milk in June and September. Because both species are frequently found in the cow's environment (Matos et al, 1991;Piessens et al, 2011), these associations might be caused by a high environmental bacterial pressure caused by warm weather conditions in summer and early autumn. In contrast, the months from September to February were associated with higher odds for Staph.…”
Section: Variance Componentsmentioning
confidence: 99%
“…However, S. aureus can persist for long periods in other body sites including the vagina, teat and skin lesions, the nares, and infected tonsils of cows [2]. Staphylococcus aureus intramammary infections in nulliparous heifers have also been reported [3] indicating that sources other than the lactating cow may serve as reservoirs of S. aureus in the dairy herd.…”
Section: Introductionmentioning
confidence: 99%